Peran Calon Tenaga Kesehatan sebagai Kader Kesehatan Remaja Srikandi (Masyarakat Peduli Akan Diabetes Melitus) - Bratajaya, Cicilia Nony Ayuningsih (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The role of nursing students as future healthcare professionals is very important, as prediabetic patients can progress to diabetes without proper treatment. They are expected to become community health role models with knowledge and skills in early detection of prediabetes. The purpose of the Prediabetes Screening Training for Trainers is to train these students to become youth health cadres of SRIKANDI (Diabetes Concerned Community). The program aims to increase participants' knowledge level from 6.64 to 8.14 by leveraging 2 days of 300 minutes of lectures, discussions, simulation methods, and a website that provides educational materials and tools for diabetes risk prevention succeeded. These results demonstrate that 14 of the 45 students who participated in the training became educators under the SRIKANDI program and are committed to forming youth health cadres who can contribute to the prevention and early detection of prediabetes.